Karakterisasi Pengelolaan Model Satuan Pendidikan Non Formal pada Kelompok Bermain Al-Fatih Makassar : Penelitian - Nur Rafifah Dwi Adzhani.R; Ahlun Ansar; Tria Melinda; Arismunandar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the characterization of the non-formal education unit model at the Al-Fatih Playgroup (KB) Makassar, which integrates Islamic values ​​into the early childhood learning process. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The results show that KB Al-Fatih implements the Independent Curriculum with a center and project approach combined with the instillation of Qur'anic character. Educators with S1 PAUD qualifications, adequate facilities and infrastructure, and a conducive learning environment support children's holistic development. The collaboratively designed learning program, based on initial assessments, has proven effective in shaping children's religious character, independence, and social skills. These findings reinforce the importance of integrating spiritual values ​​in the non-formal early childhood education model